Correlation coefficient and path analysis study among grain quality components in rice (Oryza sativa L.) - Prem Kumar. A, A. K. Sarawgi, S. B. Verulkar and R. Verma (Electronic Journal of Plant Breeding, 2010)
Correlation coefficient and path analysis study among grain quality components in rice were studied in thirty crosses. Crosses were attempted insuch a way that each line was pollinated by all pollen parents in line x tester pattern. The experimental material consisted of 5 lines viz., B6441-F-MR-6-0-0, G 9502, F7 10, BR 240, VL 16 and 6 testers viz., IR 64, Abhaya, MTU 1010, IRBL 10, IRBL 22 and LTH. In correlation studies,the following characters were found to be of importance in selection viz., hulling percentage (HP), paddy length (Pad L), head rice recovery(HRR), milling percentage (MP), brown rice length (BRL) and it also exhibited a positive interrelation among themselves. Selection based onhulling percentage (HP) is suitable, since it brings simultaneous improvement in all other quality parameter traits. Path analysis of head ricerecovery (HRR) showed that brown rice length (BRL), milling percentage (MP), hulling percentage (HP) and water uptake (WU) were mostimportant contributing characters towards the head rice recovery (HRR) based on their high positive direct effects.